2018
DOI: 10.1016/j.ebiom.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Genome Editing With CRISPR/Cas9 in a Humanized Mouse Model Ameliorates α1-antitrypsin Deficiency Phenotype

Abstract: α1-antitrypsin (AAT) is a circulating serine protease inhibitor secreted from the liver and important in preventing proteolytic neutrophil elastase associated tissue damage, primarily in lungs. In humans, AAT is encoded by the SERPINA1 (hSERPINA1) gene in which a point mutation (commonly referred to as PiZ) causes aggregation of the miss-folded protein in hepatocytes resulting in subsequent liver damage. In an attempt to rescue the pathologic liver phenotype of a mouse model of human AAT deficiency (AATD), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…In murine models, liver-directed somatic genome editing with CRISPR-Cas9 is a novel and versatile approach with therapeutic potential in metabolic disorders [103]. The proof of principle that a gene can be targeted in mammalian hepatocytes in vivo would suggest that sequence-specific gene editing might be viable in humans [104][105][106][107]. In the future, liverspecific gene editing may be used to alter hepatic gene transcription for therapeutic purposes in AD.…”
Section: Gene Silencing and Genome Editingmentioning
confidence: 99%
“…In murine models, liver-directed somatic genome editing with CRISPR-Cas9 is a novel and versatile approach with therapeutic potential in metabolic disorders [103]. The proof of principle that a gene can be targeted in mammalian hepatocytes in vivo would suggest that sequence-specific gene editing might be viable in humans [104][105][106][107]. In the future, liverspecific gene editing may be used to alter hepatic gene transcription for therapeutic purposes in AD.…”
Section: Gene Silencing and Genome Editingmentioning
confidence: 99%
“…α-1 antitrypsin (AAT) is secreted by the liver, and if the mutant allele is present, the protein aggregates in hepatocytes causing liver fibrosis, cirrhosis, and cancer and the reduction in circulating AAT also results in emphysema and Chronic Obstructive Pulmonary Disease (COPD) in the lungs. Cas9 has been used to knockout the mutant AAT gene or to knockin the normal gene in to a safe harbor site in mouse models [122][123][124]. Research has shown that dual delivery of both Cas9 targeted to ATT in combination with a donor template will knockout the mutant allele and integrate the wild-type allele, leading to expression of the wild-type AAT in mouse models [124,125].…”
Section: Looking Forward: Upcoming Areas For Gene Editor Clinical Trialsmentioning
confidence: 99%
“…Liver biopsies showed a significant decrease in AAT aggregates and a decrease in liver fibrosis and inflammation. Obviously, this study does not address the reversal of AATD pathology, but it nonetheless opens a door to research in CRISPR/Cas9 gene editing in vivo treatment to reduce mutant protein, although potential risks must be carefully investigated [ 135 ].…”
Section: Gene Therapy In Rare Respiratory Diseasesmentioning
confidence: 99%